PHYSICAL AND SPIRITUAL HEALTH IN HINDU RITUALS IN BALI - Ayu Dwita (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2025)
Hindu rituals in Bali are not only religious in nature but also embody holistic health values, encompassing both physical and spiritual dimensions. This study aims to examine the relationship between the practice of Balinese Hindu rituals and efforts to maintain and improve community health. The method employed is a qualitative approach through literature review and in-depth interviews with ritual practitioners and traditional healers. The findings reveal that rituals such as melukat (purification), usadha Bali (traditional healing), yoga, meditation, and Bhuta Yadnya function as means of self-purification, disease prevention, and energy restoration. Physically, the use of natural elements such as holy water, herbs, incense, and fire provides antiseptic, relaxation, and detoxification benefits. Spiritually, the rituals strengthen the individual’s relationship with God, ancestors, and nature, thus producing calming effects, reducing stress, and enhancing emotional balance. The concept of Tri Hita Karana serves as the philosophical foundation that integrates bodily, mental, and environmental health. These findings affirm that Balinese Hindu rituals hold significant relevance for contemporary holistic health concepts and have the potential to be developed as the basis for spiritual health tourism. Integration between traditional practices and modern medicine can further expand the benefits of rituals for both local and global communities.